2022
DOI: 10.7759/cureus.26207
|View full text |Cite
|
Sign up to set email alerts
|

Rare Case of Reversible Pulmonary Arterial Hypertension Secondary to Cyclophosphamide and Doxorubicin Chemotherapy

Abstract: Pulmonary arterial hypertension (PAH), characterized as a resting mean pulmonary artery pressure greater than 25 mmHg, is due to the narrowing of the pulmonary arteries, which can be idiopathic, inherited, or drug-related. Alkylating agents, including cyclophosphamide, are a risk factor for developing the pulmonary veno-occlusive disease. Drug-induced PAH is extremely rare. A 59-year-old female with newly diagnosed invasive ductal carcinoma of the right breast and high-grade ductal carcinoma in situ of the lef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…To date, there have been approximately only 20 case reports, which have shown possible associations between cyclophosphamide use and PAH [ [3] , [4] , [5] , [6] , [7] , [8] ]. However, only limited data were documented in these reports, and the association between the use of cyclophosphamide and the development of PAH was not necessarily evident.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To date, there have been approximately only 20 case reports, which have shown possible associations between cyclophosphamide use and PAH [ [3] , [4] , [5] , [6] , [7] , [8] ]. However, only limited data were documented in these reports, and the association between the use of cyclophosphamide and the development of PAH was not necessarily evident.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review reported by Benoit et al, in 2015 reviewed cases of chemotherapy-induced PVOD from the French PH network and reported that cyclophosphamide was used in 16 of the 37 cases they identified [ 4 ]. Aside from these 16 cases, there have been four other cases, in which PH developed following the use of cyclophosphamide [ 3 , 5 , 6 ]. Notably, in all these cases, multiple chemotherapeutic agents were used simultaneously, and ten patients underwent bone marrow transplantation; thus, the association between the use of cyclophosphamide and the development of PAH was not clearly elucidated [ [3] , [4] , [5] , [6] ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence suggests that cyclophosphamide and its metabolites cause peroxidation of cell membrane lipids. 28 A systematic review of the role of alkylating agents in the development of pulmonary hypertension, published in 2015 established that these compounds, including cyclophosphamide, are a risk factor for pulmonary veno -occlusive disease. In experimental models, cyclophosphamide exposure leads to venous remodeling, which, in turn, leads to the development of pulmonary hypertension.…”
Section: Cyclophosphamidementioning
confidence: 99%